Biotechnology revival: in situ sludge minimization in wastewater - Chen, Yiqiang; Jiang, Xu; Yang, Maosheng; Wang, Zhu (Frontiers in Microbiology, 2025)
In the face of the escalating challenge of sludge production and disposal in wastewater treatment plants (WWTPs), in situ sludge reduction biotechnology (ISRB) has recently emerged as a highly promising strategy. It not only has the potential to curtail sludge generation at its origin but also ensures the sustained efficiency of the treatment process. Several key strategies have demonstrated exceptional potential in harnessing microbial processes for sludge degradation. They encompass enzymatic hydrolysis, microbial inoculation, protozoan/metazoan predation, bacteriophage lysis, and biofilm-based manipulation. Compared to traditional methods (e.g., incineration and landfilling), these biotechnologies offer significant advantages through lower costs, reduced energy consumption, and minimal environmental impacts. The efficacy of ISRB is substantially affected by various factors, where pH, microbial shift, and nutrient conditions play crucial roles. Despite the notable progress made in this field, significant challenges persist when it comes to scaling up these technologies for more extensive and widespread applications. This review comprehensively highlights the fundamental mechanisms, application strategies, and future prospects of ISRB, including one of the first studies to introduce bacteriophage-based approaches for in situ sludge reduction, offering a novel perspective on phage-mediated sludge control. By doing so, it aims to offer in-depth insights into the role of ISRB as a sustainable solution for sludge management, paving the way for further research and development in this crucial area of environmental biotechnology.